KOORDINASI BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL DALAM PENGENDALIAN ANGKA FERTILISASI DI KOTA PEKANBARU TAHUN 2018 - Clara Irvina Ryan; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The high rate of population growth is a problem that is being faced in Indonesia. The rate of population growth often occurs in the provincial capitals in Indonesia. Pekanbaru city as the capital of Riau province also experienced a population growth rate caused by the high rate of fertilization that occurred in Pekanbaru City. To achieve a balance between the quality and quantity of population distribution and the environment as stated in Law Number 52 of 2009 concerning Population Development and Family Development, Pekanbaru City must coordinate in the field of population control and family planning in order to realize a quality population and population distribution. evenly distributed and controlled population in Pekanbaru City. Lack of coordination in population control and family planning, causes the number of fertilization rates to continue to grow and not be controlled.The purpose of this study was to determine the coordination of the BKKBN in controlling the fertility rate in Pekanbaru City in 2018 and to describe the obstacles to the coordination of the BKKBN in controlling the fertility rate in Pekanbaru City. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques.The results of this study found that communication between field lines and coordination in controlling fertility rates was still not maximized, further socialization of joint programs carried out together, and BKKBD had not been formed in Pekanbaru City. Keywords: Coordination, Fertilization, Population.